Papillary Carcinoma in a Thyroglossal Cyst: A Case Report - Andreetta, Amabile; Nagai, Gabriel Massahiro; Nagai, Hildebrando Massahiro; Nagai, Bruno Hideji; Pavaneli, Giovanni Gussi; Souza, Lucas Gabriel Leme de (Brazilian Journal of Oncology, 2025)
We herein report a case of papillary thyroid carcinoma with an unusual presentation, inside a thyroglossal cyst. An 83-year-old male patient reported a long-standing nodule persisting for over 40 years, with progressive enlargement and periodic dysphonia. The patient underwent total thyroidectomy combined with the Sistrunk procedure. Resection of the thyroglossal duct cyst and total thyroidectomy are the treatments of choice for this rare presentation. The case herein reported is deemed atypical according to the current literature, and it was managed following the existing guidelines, resulting in a satisfactory outcome.
Keywords: thyroid neoplasm; thyroid carcinoma; thyroglossal duct cyst